1999
DOI: 10.1016/s0885-3924(98)00106-7
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Goal Attainment Scaling in Chronic Pain Settings

Abstract: Although the multidimensional nature of chronic pain has been recognized since the 1960s, pain management continues to reflect a biomedical model for many chronic pain patients. The application of a biopsychosocial approach would be aided by measurement tools that reflect the multidimensional nature of pain, facilitate interdisciplinary care planning, and focus treatment on the consequences of pain that are important to patients. Goal Attainment Scaling (GAS) is an individualized health outcome measure that is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 20 publications
(22 reference statements)
1
30
0
1
Order By: Relevance
“…Some examples are studies evaluating a comprehensive day-treatment programme, 13 botulinum toxin A (BTX-A) treatment, 14 lower-extremity amputations, 15 and pain management programmes. 16,17 These studies support the hypothesis that in the field of rehabilitation medicine, GAS provides a more responsive measure than other, more conventional outcome measures (such as the Barthel Index or the Locomotor Capabilities Index).…”
Section: Reviewsupporting
confidence: 54%
“…Some examples are studies evaluating a comprehensive day-treatment programme, 13 botulinum toxin A (BTX-A) treatment, 14 lower-extremity amputations, 15 and pain management programmes. 16,17 These studies support the hypothesis that in the field of rehabilitation medicine, GAS provides a more responsive measure than other, more conventional outcome measures (such as the Barthel Index or the Locomotor Capabilities Index).…”
Section: Reviewsupporting
confidence: 54%
“…The rise in FPG with weight loss suggests that the initial reduction in energy intake decreased FPG, rather than the weight loss. 34 Participants that maintained a FPG less than 108 mg/dL for one year after the initial three month period continued to lose 3% IBW on average during this time. This weight loss outcome also supports the benefits of the diabetes diet.…”
Section: Medical Nutrition Therapy For Diabetes Self-managementmentioning
confidence: 92%
“…35 At the end of three months, a greater reduction in blood glucose was achieved by participants with a higher initial FPG and who lost more weight. 34 Results showed that on average, participants that presented with a FPG of 180 to 216 mg/dL needed to lose 28% of IBW to achieve FPG of less than 108 mg/dL. These results were positive; however, the most effective implementation methods for achieving such results are unclear.…”
Section: Type 2 Diabetes and Obesitymentioning
confidence: 99%
See 2 more Smart Citations